Overview of a Knowledge Translation (KT) Project to improve the vaccination experience at school: The CARD™ System. (29th March 2019) - Taddio, Anna; McMurtry, C Meghan; Bucci, Lucie M; MacDonald, Noni; Ilersich, Anthony N T; Ilersich, Angelo L T; Alfieri-Maiolo, Angela; deVlaming-Kot, Christene; Alderman, Leslie
Abstract: Background: Students experience fear, pain, and fainting during vaccinations at school. While evidence-based interventions exist, no Knowledge Translation (KT) interventions have been developed to mitigate these symptoms. A multidisciplinary team—the Pain Pain Go Away Team—was assembled to address this knowledge-to-care gap. This manuscript provides an overview of the methodology, knowledge products, and impact of an evidence-based KT program developed and implemented to improve the vaccination experience at school. Methods: We adapted knowledge and assessed the barriers to knowledge use via focus group interviews with key stakeholder groups involved in school-based vaccinations: students, nurses, school staff, and parents. Next, we developed project-specific goals and data collection tools and collected baseline data. We then created a multifaceted KT intervention called The CARD™ System (C-Comfort, A-Ask, R-Relax, D-Distract) to provide a framework for planning and delivering vaccinations using a student-centred approach. Selected KT tools from this framework were reviewed in additional focus groups held in all stakeholder groups. The multifaceted KT intervention was then finalized and implemented in stages in two projects including grade 7 students undergoing school vaccinations and impact on student outcomes (e.g., symptoms of fear, pain, dizziness) and process outcomes (e.g., utilization of interventions that reduce student symptoms, vaccination rate) were assessed. Results: Participants reported that improving the vaccination experience is important. Based on participant feedback, an evidence-based multifaceted KT intervention called The CARD™ System was developed that addresses user needs and preferences. Selected KT tools of this intervention were demonstrated to be acceptable and to improve knowledge and attitudes about vaccination in the stakeholder groups. In two separate implementation projects, CARD™ helped grade 7 students prepare for vaccinations and positively impacted on their vaccination experiences. CARD™ improved vaccination experiences for other stakeholder groups as well. There was no evidence of an impact on school vaccination rates. Conclusion: We developed and implemented a promising multifaceted KT intervention called The CARD™ System to address vaccination-associated pain, fear, and fainting. Future research is recommended to determine impact in students of different ages and in different geographical regions and clinical contexts.